المسؤولية التقصيرية الناجمة عن تشغيل منظومة الهواتف النقالة (دراسة تحليلية مقارنة) - حسين, زبير مصطفى; أمين, هيرو عبدالقادر محمد (Sulaimani Journal for Humanities, 2022)
Summary The mobile phone is one of the most important means of communication. And, despite its many advantages and benefits, but, it is not without negative effects that threaten society as it controverts the human right as a life and health threat, and the right of joyful life, clean and pure environment, and all of this affects the prevailing legal concepts, especially when it comes to the theory of responsibility. It creates many problems such as the problem of how to prove the damage and the causal relationship, and the problem of determining the responsible person and determining the type of responsibility and the legal basis on which this responsibility is built, and because of all these legal problems triggered by this technology, it is no longer acceptable that its use be without legal consequences, and this is to redress Damages arising from it, so that the necessary legal solutions are established to repair these damages, and due to the lack of the necessary legal regulation and the inability of the general rules of the laws in force to address them and to confront the danger of the radiation emitted from them, which of course will lead to the lack of adequate protection for human health, the environment and other living organisms, so we have chosen the subject of responsibility in tort resulting from the operation of the mobile phone system for research and study, and this study deals with the legal aspects of tortious liability as a basis for the liability resulting from those damages and its elements as well as the issue of neighbors causing the damage, and we reached a number of conclusions and recommendations, the most important of which is to ensure compensation for the injured person based on the rules of civil liability and that established as a Warranty theory, as well as the inadequacy of the general rules contained in the civil law to protect the victim due to nature, the specific damage resulting from the operation of the mobile phone system is difficult to prove because it takes a long time to be discovered, and it proposed to amend the draft Iraqi media and communications law so as to adopt a set of other texts in order to provided adequate protection for those who are affected and in a way that can include and apply its rules to modern technological problems and their treatment especially in the field of electromagnetic damage.